Understanding the Potential of CBD for Health Benefits: An Overview - Santos, Ivan; Oliveira, Maria Beatriz Prior Pinto; Casas, Ana; Fidalgo Lopez, Javier; Almeida, Hugo (Current Drug Discovery Technologies, 2025)
Cannabinoids are compounds with increasing scientific interest, particularly due to their interaction with the endocannabinoid system via CBR1 and CBR2 receptors. They can interfere with appetite, pain, and sleep or develop mood changes in the individual. Cannabidiol (CBD) is a well-known cannabinoid with potential benefits, including reducing epilepsy seizures, alleviating anxiety and obsessive-compulsive disorder (OCD) symptoms, aiding in Tourette Syndrome (a neurodevelopmental disorder), depression, sleep disorders, and promising in the treatment of cancer, pain relief, and heart health. Although generally safe, CBD can have side effects, including drug metabolism interference, fertility, and liver function. In addition, it can be administered by oral, sublingual, transdermal, or inhalation via each one with different bioavailability. The application of nanotechnology, specifically through colloidal carrier systems, holds promising potential for maximizing CBD's efficacy and pharmacological profile. There are reported CBD extraction methods using ethanol, carbon dioxide, deionised water, and non-polar oils like olive or coconut oil. Green extraction methods have gained popularity due to their higher yields, shorter extraction time, and reduced costs. A specific dose with the desired effects is challenging due to individual factors, with most studies suggesting a range between less than 1 and 50 mg/kg/d. This review aims to explore the principles of CBD-based products development, focusing on extraction methods and purification processes of this cannabinoid for tinctures, topicals, and other pharmaceutical forms, as well as further research to attain the objectives.
Keywords: nanotechnology